Untold Stories of Moral Injury: What We Are Learning—And Not Learning—From Military Veterans in Transition - Buechner, Barton David (Frontiers in Communication, 2020)
For nearly two decades, Military veterans of many nations have struggled while returning from wartime service in Afghanistan and Iraq. Despite best efforts to welcome these service members home and provide access to educational and health benefits, many of them report a difficulty in relating to fellow citizens and institutions upon their return. One indicator of this sense of alienation is the growing number of suicides among this population, now exceeding the number of casualties of combat service itself. Thwarted ability to communicate and therefore participate in post-service social life is increasingly recognized as a significant risk factor for suicide It has never been easy for military veterans to talk about combat experiences. However, what we are seeing now points towards a deeper and more systemic issue that is not necessarily connected to specific experiences of combat trauma, but instead rooted in cultural and moral misalignments, or “moral conflict” that can lead to damage to the underlying moral structures, or “moral injuries.” These moral injuries may include perceived personal failings or culpability; a sense of futility in the political limitations of military missions, or perceived betrayals of trust by those in authority. Many veterans also point to a lack of shared values and principles among citizens, and within social institutions and media, as one reason for the difficulty of post-service reintegration. Moral injuries in this sense have further existential implications, with important (but often unheard) messages for our entire society. As a way of inviting communication scholars into this conversation, we present several models drawn from the Coordinated Management of Meaning (CMM) Theory to look at the way that moral injuries are “made” in misaligned communication between returning service members and families, institutions, and others at both the population level and in community settings. Mental health implications are drawn Adlerian psychology, a body of psychological theory that shares a social constructionist orientation with CMM. We then discuss the significance of these intersections in communication and mental health theory and practice, and implications for looking more closely at social connections and communication as key components of well-being and coherence.